(untitled) (London Journal of Medical and Health Research, 2025)
Cypermethrin, a pyrethroid insecticide, is known for its effectiveness against pests but has raised concerns about reproductive toxicity, fertility issues, and developmental issues in offspring. This review explores cypermethrin’s reproductive toxicological effects, identifying biological and molecular mechanisms, evaluating in vitro and in vivo studies, and highlighting potential long-term consequences on subsequent generations. A systematic literature review was conducted, focusing on peer-reviewed articles, toxicological reports, and relevant studies that explore the impact of cypermethrin on reproductive health. Databases such as PubMed, Scopus, and Google Scholar were searched using keywords related to cypermethrin, reproductive toxicity, endocrine disruption, and developmental effects. Studies selected for inclusion had to meet stringent criteria regarding experimental design, exposure levels, and outcome measures. Cypermethrin, an insecticide, has been found to disrupt reproductive health through various mechanisms. It interferes with hormone synthesis, leading to hormonal imbalances and sexual development issues. Cypermethrin exposure also results in oxidative stress, compromising gamete quality and reproductive function. Increased apoptosis in germ cells can lead to reduced sperm quantity and quality, impacting male fertility and female fertility. Cypermethrin exposure during critical growth periods can cause malformations and impaired development in offspring, posing risks to population viability and biodiversity. These mechanisms highlight the need for cautious regulation and deeper understanding of cypermethrin’s impact on reproductive health. Cypermethrin, a common pest in agriculture and residential areas, poses significant reproductive health risks through endocrine disruption, oxidative stress, and cellular apoptosis, necessitating further research for safe exposure levels.